Beckman RR-2 Respiratory Recorder
This image shows the graphical print-out of the instrument's readings. A respiratory recorder records both oxygen and carbon dioxide levels during respiration.
Keywords: Respiration; Medical electronics--Equipment and supplies; Oxygen--Measurement; Respiration--Measurement; Carbon dioxide--Measurement; Beckman Instruments, Inc.